Factors affecting Sharī'ah audit quality in Islamic banking institutions of Pakistan: A theoretical framework - Abdul Rashid; Muhammad Saarim Ghazi (Islamic Economic Studies (IES), 2021)
Purpose The objective of this study is to present a theoretical framework, which helps ascertain the meanings of the Sharī'ah audit quality and identify the factors that affect it. Design/methodology/approach The current literature of conventional and Islamic finance on audit quality is critically reviewed to propose the theoretical framework for the quality of Sharī'ah audit. Findings The paper suggests that for a better Sharī'ah compliance at Islamic banking institutions (IBIs), the role of audit practitioners is very much indispensable. The competency of the practitioner is one of the important factors that affect the quality of the Sharī'ah audit. Assessment and identification of Sharī'ah risk in different financial arrangements, contracts and transactions require a unique competency on the part of the auditor, that is, gripping Sharī'ah law besides traditional assurance skills and techniques. Practical implications The Sharī'ah compliance is one of the primary objectives of IBIs, which works at the conceptual level, product development and implementation level, various business models and governance level. Sharī'ah audit function, internal or external, is an important component of Sharī'ah governance framework and provides an independent assessment of IBIs' compliance with the Sharī'ah rules and principles and helps in managing the Sharī'ah non-compliance risk and ensuring sound internal Sharī'ah control system. Originality/value The paper proposes a theoretical framework for defining the Sharī'ah audit quality and determining the factors that are significant in affecting the Sharī'ah audit quality in the IBIs of Pakistan.
Keywords: G3; M4; 330; Islamic banking; Sharī'ah audit quality; Sharī'ah compliance; Sharī'ah governance; Sharī'ah risk